Analysis of Accountability and Effectiveness in the Management of BOS Funds in Meeting School Needs - Andi Nuraulia; Abd. Hafid (Penerbit Jurnal Indonesia, 2025)
This research analyzes the accountability and effectiveness of BOS fund management at UPT SD Inpres 12/79 Ujung. The research objective is to determine the extent to which BOS fund management meets transparency and accountability standards, as well as to evaluate the effectiveness of its use in supporting operations and improving education quality. This study employs a qualitative descriptive method with a field approach through interviews. Data analysis techniques include data reduction, data presentation, and drawing and verification of conclusions. The research results show that BOS fund management has reflected accountability and effectiveness principles. Funds are managed based on RKAS resulting from deliberations between the principal, teachers, treasurer, and school committee. Transparency is realized through recording, routine reporting, and information openness. Fund usage is well-targeted to support school operations, teacher training, provision of learning facilities, and facility maintenance. This management has been in accordance with Ministry of Education regulations and educational management principles, namely efficiency, participation, and evaluation. This research emphasizes the importance of transparent and accountable fund governance to achieve optimal education quality.